Bicaudal C is required for the function of the follicular epithelium during oogenesis in Rhodnius prolixus - Pascual, Agustina; Vilardo, Emiliano Salvador; Taibo, Catalina Beatriz; Sabio Y Garcia, Julia Veronica; Rivera Pomar, Rolando (Springer, 2021)
The morphology and physiology of the oogenesis have been well studied in the vector of Chagas disease Rhodnius prolixus. However, the molecular interactions that regulate the process of egg formation, key for the reproductive cycle of the vector, is still largely unknown. In order to understand the molecular and cellular basis of the oogenesis, we examined the function of the gene Bicaudal C (BicC) during oogenesis and early development of R. prolixus. We show that R. prolixus BicC (Rp-BicC) gene is expressed in the germarium, with cytoplasmic distribution, as well as in the follicular epithelium of the developing oocytes. RNAi silencing of Rp-BicC resulted in sterile females that lay few, small, non-viable eggs. The ovaries are reduced in size and show a disarray of the follicular epithelium. This indicates that Rp-BicC has a central role in the regulation of oogenesis. Although the follicular cells are able to form the chorion, the uptake of vitelline by the oocytes is compromised. We show evidence that the polarity of the follicular epithelium and the endocytic pathway, which are crucial for the proper yolk deposition, are affected. This study provides insights into the molecular mechanisms underlying oocyte development and show that Rp-BicC is important for de developmental of the egg and, therefore, a key player in the reproduction of this insect.